Angry youth comix - Ryan, Johnny 1970- (Fantagraphics Books, 2015)
"For the first time, all fourteen issues of Johnny Ryan's career-defining comic book series Angry Youth Comics (2000-2008) are collected in one place: all the comics, the covers, and even the contentious letters pages, in one toilet-ready brick. Johnny Ryan's utterly unpretentious, taboo-tackling is an infectious and hilarious bombardment of political incorrectness, taking full advantage of the medium's absurdist potential for maximum laughs. In an age when the medium is growing up and aspiring to more mature and hoity-toity literary heights, Ryan builds on the visceral tradition that cartooning has had on our collective funny bone for over a century."--Amazon.com
"The material contained herein was originally published by Fantagraphics Books as a fourteen issue comic book series, Angry Youth Comics, from 2001 to 2008."
Keywords: Ryan, Johnny -- 1970-; Underground comic books, strips, etc; Graphic novels; Underground comics; Comics (Graphic works); Comic